Women and new labour : engendering politics and policy? - Annesley, Claire; Gains, Francesca; Rummery, Kirstein (Policy, 2007)
New Labour have set themselves up to specifically address women's issues and attract women voters, but how successful have they been? This book offers an analysis of New Labour's politics and policies from a gendered perspective.